PERBEDAAN HASIL BELAJAR SISWA KELAS VII SMP NEGERI 9 AMBON MENGGUNAKAN MODEL PEMBELAJARAN LAPS-HEURISTIC DAN MODEL PEMBELAJARAN MEANDS-ENDS ANALYSIS DIPADUKAN DENGAN MEDIA MOVIE KONSEP EKOSISTEM - Frensca A Jacob; H Tuaputty (Program Studi Pendidikan Biologi FKIP Unpatti, 2019)
Background: To achieve learning objectives, teachers are required to be able to choose and integrate learning models and learning media that are suitable for application in a particular concept. Although the development of the learning model has undergone a change, in reality teachers still have difficulty in determining the learning model that is suitable to be applied at an educational level. Method: The study was conducted on 18 September - 18 October 2018 using descriptive methods, student learning outcomes were seen through the final grades assessed based on cognitive (LKS), affective and psychomotor aspects and pre-post test scores. Measurement data were analyzed using t test formula. Results: Based on the t test, the results of tcount 14.066 and ttable 1.658, tcount> ttable, then the null hypothesis (HO) is rejected and the alternative hypothesis (Ha) is accepted. This shows that there are differences in learning outcomes of class VII students of SMP Negeri 9 Ambon using Laps-Heuristic learning models and Meands-Ends Analysis combined with Movie media. Conclusion: There are differences in student learning outcomes by using Laps-Heuristic and Meands-Ends Analysis learning models for the ecosystem concept in class VII Ambon 9 State Junior High School. Meands-Ends Analysis learning is more effective for improving student learning outcomes than Laps-Heuristic learning models.